Simultaneous Subcutaneous and Intranasal Administration of a CAF01-Adjuvanted Chlamydia Vaccine Elicits Elevated IgA and Protective Th1/Th17 Responses in the Genital Tract - Wern, Jeanette Erbo; Sorensen, Maria Rathmann; Olsen, Anja Weinreich; Andersen, Peter; Follmann, Frank (Frontiers in Immunology, 2017)
The selection of any specific immunization route is critical when defining future vaccine strategies against a genital infection like Chlamydia trachomatis. An optimal chlamydia vaccine needs to elicit mucosal immunity comprising both neutralizing IgA/IgG antibodies and strong Th1/Th17 responses. A strategic tool to modulate this immune profile and mucosal localization of vaccine responses is to combine parenteral and mucosal immunizations routes. In this study we investigate whether this strategy can be adapted into a two-visit strategy by simultaneous subcutaneous and nasal immunization. Using a subunit vaccine composed of Chlamydia trachomatis antigens adjuvanted with CAF01, a Th1/Th17 promoting adjuvant, we comparatively evaluated antigen-specific B and T cell responses and efficacy in mice following subcutaneous (SC) and simultaneous subcutaneous and nasal immunization (SIM). We found similar peripheral responses with regard to IFN and IL-17 producing antigen-specific splenocytes and IgG serum levels in both vaccine strategies but in addition, the SIM protocol also led to antigen-specific IgA responses and increased B and CD4+ T cells in the lung parenchyma, and in lower numbers also in the genital tract. Following vaginal infection with Chlamydia trachomatis we observed that SIM immunization gave rise to an early IgA response and IgA-secreting plasma cells in the genital tract in contrast to SC immunization but we were not able to detect more rapid recruitment of mucosal T cells. Interestingly, although SIM vaccination in general improved mucosal immunity we observed no improved efficacy against genital infection compared to SC, a finding that warrants for further investigation. In conclusion, we demonstrate a novel vaccination strategy that combines systemic and mucosal immunity in a two-visit strategy.